Use of arbuscular mycorrhizal fungi (AMF) in the nutrition of Leucacephala leucocephala (Lam.) De wit for forage production - Lázaro J. Ojeda; Ramón A. Rivera; Juan J. de la Rosa (Temas Agrarios, 2023)
At present, the use of biofertilizers and protein plants in the nutrition of pastures and forage has increased. The investigation was carried out in the University Center of the municipality of Cumanayagua, county of Cienfuegos, Cuba with the objective of evaluating the response of Leucaena leucocephala (Lam.) De Wit to the inoculation of different arbuscular mycorrhizal fungi (AMF) strains. The experiment was carried out in polyethylene bags. The experiment used a random blocks design with three replicates and the following treatments: #1. Soil (Control treatment, without inoculation and NPK application), #2. Soil + inoculation with the AMF strain F. mosseae/INCAM-2, #3. Soil + inoculation with the AMF strain G. cubense/INCAM-4) and #4. Soil + NPK fertilization at plant establishment application of NPK (25, 40 y 120 kg ha-1 de N, P2O5 y K20) + N at each cut at 70% of the initial dose. The inoculation with AMF was simultaneous for all treatments. A establishment cut and five successive cuts were performed, with 51.33 average days between them. The biomass production, the content of gross protein of L. leucocephala in each harvest and the cumulative total, as well as mycorrhizal effectiveness, were quantified. L. leucocephala positively responded to F. mosseae/INCAM-2 inoculation. Biomass production for cut increased between 31,50 % (Treatment #2) y 19,40 % (Treatment #3) with respect to control treatment. Inoculation with F. mosseae/INCAM-2 showed higher mycorrhizal effectiveness. The highest value in gross protein was obtained in the variant with mineral fertilization and the inoculated variants overcame the control treatment, with better performance than treatment # 2 ( Soil+ Funneliformis mosseae/INCAM-2).